PERSEPSI MASYARAKAT SEMENDE TERHADAP PEMBAGIAN HARTA WARISAN DENGAN SISTEM TUNGGU TUBANG (Studi kasus di Desa Sukananti Kec. Way Tenong Kab. Lampung Barat) - Saputra, Arwin Rio; Wirawan, Bintang (JURNAL SOSIOLOGI, 2013)
This study aims to clarify the perception of the public towards inheritance Semendeâs with tunggu tubang system. Inheritance by tunggu tubang started many people questioned by Semende about the level of justice, and with the development of the times many of them are tunggu tubang status as an objection to these states.Results of this research indicate that perception of Semendeâs community about system tunggu tubang are different. It depends on the individual self-awareness in the community Semendeâs in the roles and status of each well. Preservation of indigenous tubang waiting to awake or not also depends on the consciousness of the individual in society Semendeâs themselves to be able to keep the heritage of their ancestors.Â Keyword: perception, semendeâs community, heritage, tunggu tuban.